Species Composition, Parous Rate, and Infection Rate of Anopheles Mosquitoes (Diptera: Culicidae) in Bahir Dar City Administration, Northwest Ethiopia. Issue 4 (3rd April 2021) - Getaneh, Abel; Yimer, Mulat; Alemu, Megbaru; Dejazmach, Zelalem; Alehegn, Michael; Tegegne, Banchamlak
Abstract: Anopheles mosquitoes are the main vectors of malaria. There is little information on the current entomological aspects of Anopheles mosquitoes in Amhara region of northwestern Ethiopia. Therefore, the aim of this study was to assess the prevailing species composition, parous rate, and infection rate of Anopheles mosquitoes in the Bahir Dar city administration. A community-based cross-sectional study was conducted from January through July 2020. For this, six Centers for Disease Control and Prevention light traps (three traps indoor and three traps outdoor) were used to collect adult female Anopheles mosquitoes. The species were morphologically identified, and the parous and infection rates were determined via dissection of ovaries and salivary gland, respectively. A total of 378 adult female Anopheles mosquitoes comprised of three species ( Anopheles d'thali, Anopheles rhodesiensis, and Anopheles gambiae complex) were collected and identified at the study sites. Anopheles rhodesiensis was the predominant species accounting for 90% of all collections at the Zenzelima site, followed by An. gambiae complex (6.5%). In contrast, An. gambiae complex was the predominant species at the Tis Abay site, comprising 94% of captures. The overall parous and infection rates were 35 (62.5%) and 1 (2.9%), respectively.